Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00125-011-2264-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased neuronal nitric oxide synthase dimerisation is involved in rat and human pancreatic beta cell hyperactivity in obesity

Abstract: Aims/hypothesis Pancreatic beta cell hyperactivity is known to occur in obesity, particularly in insulin-resistant states. Our aim was to investigate whether changes in neuronal nitric oxide synthase (nNOS) function affect beta cell compensation in two relevant models: the Zucker fa/fa rats and pancreatic islets from obese humans. Methods Glucose-induced insulin response was evaluated in the isolated perfused rat pancreas and in human pancreatic islets from obese individuals. Expression of nNOS (also known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Therefore the earlier observations together with our present data indicate that the basal nNOS expression plays a regulatory role in insulin secretion, probably by preventing possible episodes of hyperinsulinemia, but is not disadvantageous for the beta cell function or does not promote beta cell vulnerability. A decreased catalytical activity of nNOS and its relocalization have been shown to be involved in the hyperactivity of beta cells from insulinresistant rats and also from human islets isolated from obese individuals [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the earlier observations together with our present data indicate that the basal nNOS expression plays a regulatory role in insulin secretion, probably by preventing possible episodes of hyperinsulinemia, but is not disadvantageous for the beta cell function or does not promote beta cell vulnerability. A decreased catalytical activity of nNOS and its relocalization have been shown to be involved in the hyperactivity of beta cells from insulinresistant rats and also from human islets isolated from obese individuals [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus freshly isolated islets from both young and adult hyperglycemic ob/ob mice are almost devoid of iNOS activity and display markedly reduced ncNOS activity coincident with a high rate of insulin release and the absence of a beta-cell demise in spite of their longstanding obesity and hyperglycemia [30]. Furthermore, it was recently shown that islets from obese human individuals as well as from obese Zucker fa/fa rats displayed a drastic increase in catalytically inactive ncNOS enzyme protein coincident with an augmented glucose-stimulated insulin release [12]. These data thus strengthen our hypothesis of ncNOS-derived NO as an important negative modulator of glucose-stimulated insulin release.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal constitutive NO-synthase (ncNOS, also named nNOS or NOS1) is constitutively expressed in the beta-cells of both rodent and human islets[1012], while the inducible NOS (iNOS, also named NOS2) is expressed mainly at high persisting glucose levels and/or after cytokine impact on the beta-cell [9,1315]. We have shown in normal rodent islets that ncNOS-derived NO is immediately released upon glucose stimulation both in vivo and in vitro [6,7], while iNOS-derived NO is apparent first at the latter part of a 60 min exposure to an approximate glucose concentration of ≥9–10 mmol/l [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In type 2 diabetes mellitus (T2DM) Chinese hamsters, reduced islet innervation was reported, as was the remodelling of the mouse islet sympathetic innervation in diabetic injuries . To date, there is no data on how nitrergic neurons are involved but abnormalities in islet NO production have been reported in T2DM Goto‐Kakizaki rats and in islets of obese Zucker fa/fa rats and humans …”
Section: Introductionmentioning
confidence: 99%